Size controllable synthesis and multicolor fluorescence of SiO2:Ln3+(Ln=Eu, Tb) spherical nanoparticles. Issue 5 (1st April 2017) - Chen, Jie; Zhou, Xiuqing; Sheng, Ye; Xie, Xiaoming; Abualrejal, Murad M.A.; Chang, Meiqi; Shi, Zhan; Zou, Haifeng
Abstract: A series of size controllable Tb 3+ and/or Eu 3+ activated nano-sized silica phosphors have been successfully synthesized through a facile sol-gel method. The structure, morphology, compositions, and luminescence properties of as-prepared samples were well investigated using X-ray diffraction (XRD), scanning electron microscope (SEM), energy dispersive spectrometer (EDS), X-ray photoelectron spectroscopy (XPS), Brunauer-Emmett-Teller (BET) and photoluminescence spectroscopy (PL). The results showed that all as-prepared samples were spherical nanoparticles but the sizes reduced gradually with the temperature increased from 25 °C to 65 °C, which was contrary to the BET surfaces as well as the luminescence intensity. Under ultraviolet excitation, the SiO2 :Ln 3+ (Ln=Eu, Tb) spherical nanoparticles showed characteristic red and green emissions corresponding to f-f transition of Eu 3+ and Tb 3+, respectively. Moreover, the luminescence emissions of samples can be tuned from green to yellow, orange and red by co-doping the Tb 3+ and Eu 3+ ions in different concentration ratio into the SiO2 host due to the efficient dipole–dipole energy transfer mechanism from Tb 3+ to Eu 3+ under 377 nm excitation. These results show that as-prepared phosphors may find potential applications in color display fields.